MEDIA DAN KOMODIFIKASI KEBERPIHAKAN POLITIK : ANALISA EKONOMI POLITIK MNC MEDIA GROUP - FIRLY RACHMAH ISTIGHFARIN; MAGVIRA YULIANI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The mass media industry since the reform era has changed significantly, freedom of press had been widely opened, furthermore with technological advances and the birth of social media. Competitiveness in the mass media industry is tougher in market dominance. Media owners in Indonesia are competing to penetrate the market and secure their business positions by joining the politics, even the media itself is allegedly used by the owner as a commodity that can gain profit and become a propaganda’s tool for certain political interests. MNC Media Group is a media owned by Hary Tanoesoedibjo, a businessman and politician from the Perindo Party. Then, how does Hary Tanoesoedibjo commodify the MNC Media Group? Theory of Political Economy of Media, Vincent Moscow (1996) discusses the concept of commodification, explaining how the process of transforming goods and services with their use value into a policy that has an exchange rate in the market. The analysis by the author is to see at the relationships behind the production, consumption and distribution processes carried out by the MNC Media Group. Commodification of MNC Media Group is carried out through three types of commodification, namely; commodification of contents, audiences and workers. Commodification is made using the economy and politics by its owner, Hary Tanoesoedibjo which is carried out in the form of an integrated business unit, or a synergy between all business units, builing a positive image for the owner using legitimacy of the power relations.